Desvios ortográficos recorrentes na escrita de alunos de 6º ano e sua correlação com o ensino da ortografia nos anos iniciais - Alcântara, Francisca Cátia da Silva Gomes (2023)
We live in a graphocentric society, where writing is widely valued. Mastering writing according to spelling conventions is an essential factor for citizens to achieve their academic and professional advancement. In this way, it is the role of the school to promote this learning. It is common for students to achieve high levels of learning with spelling difficulties that should have already been overcome in the initial years of teaching.In view of the above, this research assumed as a general objective to investigate, in the early years of elementary school, the approaches related to the most recurrent spelling inaccuracies in the written production of students of the 6th year, namely: the elision of <r> each end of verbs in the infinitive, the competition of graphemes to represent the voiceless alveolar fricative /s/, and the competition of graphemes to mark nasalization. To investigate how spelling is taught in the early years, especially these three cases of inaccuracies, we analyzed the textbooks from 1st to 5th grade of the Ápis series; we conducted interviews and administered questionnaires with teachers, using official documents such as the PCN and the BNCC as a basis for analysis, as well as authors such as Morais (1998; 2005; 2007), Cagliari (1999; 2005), Roberto (2006), among others who defend a reflective and systematic teaching of spelling. With regard to the textbook, we found that the series presents a methodological proposal that is based on reflection and systematization, with some exceptions. However, the amount of spelling activities is insufficient for the consolidation of learning, especially with regard to the inaccuracy identified as the most recurrent, on which the collection presents only two activities divided into two volumes. The interviews and questionnaires carried out with the teachers revealed that, although these professionals are open to new teaching possibilities, they still use traditional teaching methods. Thus, we concluded that the teaching approach used in the early years can contribute to the occurrence of spelling inaccuracies identified in the 6th year of the final years. Thus, as a way of contributing to a reflective and systematic teaching of spelling, we created a Pedagogical Workbook with the aim of helping students and teachers to overcome the spelling difficulties dealt with in this research. The Workbook has twenty activities, distributed as follows: two introductory activities that aim to reflect on the different situations of language use, taking linguistic variation, linguistic prejudice and standard norms as their theme; six activities to work on the use of the letter <R> at the end of verbs in the infinitive; six activities on the use of <s>, involving grapheme and phoneme, and six activities that address nasalization, focusing on the regularities of using <m> before and and the use of <am> and <ão> in verb forms in the past and future tenses. The aforementioned Workbook is based on a systematic and reflective teaching, which was defended throughout this dissertation and took into account the spelling difficulties identified in the groups surveyed in the context of this researc